Formulation of Natural Food Coloring Granules from Dragon Fruit Peel Extract (Hylocereus polyrhizus) and Effectiveness Test in Reducing Blood Glucose Levels - Rudang, Singgar Ni; Ginting, Indra; Andry, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Anthocyanin is one of the many compounds in dragon fruit skin that can be used as an antioxidant. Dragon fruit skin can also lower blood glucose levels. The fact that cases of diabetes mellitus are increasing every year shows that this disease needs serious treatment. This study aims to make dragon fruit skin extract formulated in the form of granules and make dragon fruit skin extract granules that meet the requirements as natural food coloring and to determine the content and effectiveness of dragon fruit skin extract (Hylocereus polyrhizus) which can lower blood glucose levels. This research method is experimental. The One Way Anova test and the Tukey HSD post-hoc test were used to analyze the data. The outcomes showed that there were 9 granule recipes that met the assessment test necessities. After being induced by 20% fructose solution, the glucose level study revealed that the treatment of dragon fruit skin extract at 100, 200, and 400 mg / kgBW was able to lower blood glucose levels in test animals. Winged serpent natural product skin concentrate can be formed as granules. Equations 2 and 3 produce the best tone. The consequences of the review reasoned that winged serpent natural product skin remove (Hylocereus polyrhizus) at dosages of 100, 200 and 400 mg/kgBW was viable in decreasing blood glucose levels in guinea pigs prompted by 20% fructose arrangement and a portion of 200 mg/kgBW gave an impact of lessening blood glucose levels that was practically equivalent to the positive control.